Carbon and nitrogen pools in the soil profile after seven years of nitrogen management and cover crop rotation in an Oxisol from Southern-Brazil - Mira, Acácio Bezerra de (2020)
Maize production in Southern Brazil relies in intensive nitrogen (N) fertilization to maximize maize yield. Excessive N fertilization may negatively influence soil carbon (C) and N dynamics. However, there is still controversy in literature about the effect of N fertilization on soil organic matter (SOM), and the long-term effect of continuous N rates on C and N distribution in soil profile is still understudied in subtropical Oxisols. In this study we investigate the effect of seven-year N fertilization on C and N distribution in a no-till soil profile under different cover crop rotations. We hypothesize that applying high N rates in maize promotes subsoil N accumulation and depletes soil C storage, and this effect may be more intense when legumes are used as cover crop. A field experiment has been conducted for seven years, under a randomized block design, in a split-plot arrangement. Two biannual crop rotations were allocated to the main plots with the following winter/summer successions: (i) black oat/maize, wheat/soybean; and (ii) field pea/maize, wheat/soybean. Nitrogen rates (0, 70, 140, 210 kg ha-1 N) were top-dressed to the subplots whenever maize was grown (V4 stage). Soil samples until 1.0-m deep were analyzed for total N (TN), total organic C (TOC), soluble inorganic N (SIN), soluble organic N (SON), mineralizable C (MINC), and permanganate oxidable C (POXC). Soil bulk density was measured to calculate C and N stocks. Despite field pea\'s potential of biological N fixation, top-dress N fertilization increased subsoil SIN accumulation only in black oats\' rotation. Field pea\'s rotation also showed a lower average subsoil N accumulation. This is probably associated to a higher N extraction due to the improved grain yields of maize grown after field pea. Nitrogen fertilization resulted in higher topsoil C stocks in both crop rotations but decrease subsoil C storage in field pea\'s rotation. The homogeneous SON distribution in soil profile in both crop rotations and the reduced POXC concentration below 0.2 m deep indicate that lower subsoil C stocks are more related to a shallower plant rooting when high N rates are applied than to a possible priming effect induced by extra N availability. Including a legume as winter cover crop before maize in maize/soybean rotations has potential to improve maize grain yield and reduce N fertilizer demand right in the first year. This reduction is recommended since applying high N rates may decrease soil C storage and increase subsoil N enrichment in Oxisols under no-tillage.